Comparative Effectiveness of Ultrasound-Guided Intratendinous Prolotherapy Injection with Conventional Treatment to Treat Focal Supraspinatus Tendinosis - George, John; Li, Shyan Ch'ng; Jaafar, Zulkarnain; Hamid, Mohamad Shariff A. (Hindawi Publishing Corporation, 2018)
Objective. To evaluate the efficacy of dextrose prolotherapy injection for focal supraspinatus rotator cuff tendinosis via outcomes such as functional score, range of movement, and real-Time ultrasound parameters. Materials and Methods. 12 adult patients with focal supraspinatus tendinosis recruited after they had less than 30% improvement in functional (DASH) scores after one month of physiotherapy following initial presentation. Seven patients had 0.5-1.0 ml of prolotherapy injection (12.5% dextrose, 0.5% lignocaine) injected into the area of focal tendinosis under ultrasound guidance. Meanwhile, five patients continued standard physiotherapy with no intervention performed. Regional area of echogenicity in decibels, DASH, range of movements of the shoulder, pain, and sleep scores were measured at baseline and at 12 weeks. Results. The prolotherapy group showed significant improvement in shoulder abduction (p=0.030) and an improvement in sleep score (p=0.027). The echogenicity of area of tendinosis significantly increases at the end of treatment (p=0.009). However, there was a nonsignificant reduction in pain score in the injection group (43.5%) and in the control group (25%) at 12 weeks (p>0.005). Conclusion. Ultrasound-guided intratendinous prolotherapy injection significantly improves patient's range of abduction and improves sleep within 12 weeks of treatment compared to conventional physiotherapy management. Trial Registration. This study was registered under Current Controlled Trials (UK) and given International Standard Randomised Controlled Trial Number (ISRCTN) of 43520960.